Estimation of dynamic water demand function: the case of Istanbul - Tastan, Hueseyin (TAYLOR & FRANCIS LTD, 2018)
This paper empirically examines the determinants of water demand in the megacity of Istanbul, Turkey, using a dynamic framework. An autoregressive distributed lag model is developed to estimate both short-run and long-run water price elasticities using aggregated monthly water consumption data. Empirical analysis reveals that a long-run stable demand relationship exists between water consumption and water price along with several non-price variables. Results indicate that water demand in Istanbul is price-inelastic with an estimated price elasticity of -0.15 in the short run, and around in the long run. Empirical results also suggest that the block increasing tariff regime is more effective in urban water demand management than the single volumetric price regime. Overall, the empirical findings of this study imply that price can potentially be used as an effective policy tool for water demand management in Istanbul.
Keywords: Water demand; water price elasticity; Istanbul; water management; LONG-RUN; MANAGEMENT; PRICE; Water Resources